2009
DOI: 10.3109/10408440903279946
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and human health assessment of decabromodiphenyl ether

Abstract: Recent public concern has focused on potential reproductive and developmental effects from exposure to low levels of bisphenol A (BPA, CAS number 80-05-7). Two previous published reviews (Gray et al., 2004a; Goodman et al., 2006) conducted weight-of-evidence evaluations of in vivo reproductive/developmental toxicity from BPA exposure < or = 5 mg/kg-d based on studies published through February 2006. Here, an update of those analyses presents additional relevant studies that were published through July 25, 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…We agree that no adverse biological effects of BDE-209 have also been reported in the literatures (Biesemeier et al, 2011;Hardy et al, 2002Hardy et al, , 2009Johnson et al, 2010), however, a comprehensive review of the toxicity of BDE-209 is beyond the scope of our paper. The purpose of our paper was to demonstrate the maternal transfer of BDE-209 and its metabolites to sucking rat pups after prenatal and/or postnatal exposure.…”
Section: Response To the Letter From Biesemeier Et Alsupporting
confidence: 81%
“…We agree that no adverse biological effects of BDE-209 have also been reported in the literatures (Biesemeier et al, 2011;Hardy et al, 2002Hardy et al, , 2009Johnson et al, 2010), however, a comprehensive review of the toxicity of BDE-209 is beyond the scope of our paper. The purpose of our paper was to demonstrate the maternal transfer of BDE-209 and its metabolites to sucking rat pups after prenatal and/or postnatal exposure.…”
Section: Response To the Letter From Biesemeier Et Alsupporting
confidence: 81%
“…The early works regarding BDE-209 were conducted in rats fed this compound at high dietary concentrations (> 230 mg/kg feed) and suggested that BDE-209 was poorly absorbed from the gastrointestinal tract (NTP, 1986;ATSDR, 2004;Hardy et al, 2009). However, in a more recent study carried out in rats dosed by gavage with radiolabelled BDE-209 (2.8 mg/kg b.w.)…”
Section: Bde-209mentioning
confidence: 99%
“…In 2000, the U.S. National Research Council issued a chronic oral reference dose 1 for DecaBDE of 4 mg/(kg ⅐ day) (National Research Council, 2000). This value was derived from DecaBDE's extensive toxicology database, which includes evaluations on subchronic and chronic toxicity, development, reproduction, mutagenicity, and carcinogenicity (Norris et al, 1973(Norris et al, , 1974Kociba et al, 1975;National Toxicology Program, 1986;el Dareer et al, 1987;Hardy et al, 2002Hardy et al, , 2009). The European Union (EU) independently reviewed these same studies and concluded that the manufacture and use of DecaBDE did not present a risk to human health (European Commission, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Until the report by Viberg et al (2001), DecaBDE's mammalian toxicology database supported its safe use as a flame retardant, as evidenced by no-observed-effect levels and no-observed-adverseeffect levels of Ն1000 mg/(kg ⅐ day) in repeated-dose studies (Hardy et al, 2009). DecaBDE's limited bioavailability 3 was considered a factor in its general lack of mammalian toxicity (National Toxicology Program, 1986;el Dareer et al, 1987;Zhou et al, 2001).…”
mentioning
confidence: 99%